Lattice gas and thermodynamics in models of heredity - Ganikhodjaev, Nasir (2011)
Quadratic stochastic operators frequently arise in many models of mathematical genetics. We propose a constructive description of quadratic stochastic operators that allows a natural introduction of thermodynamics in studying some models of heredity. This construction allows one to elicidate the role of the absolute temperature in the analysis of quadratic stochastic operators.